An investigation into how grade 9 learners make sense of the fermentation and distillation processes through exploring the indigenous practice of making the traditional alcoholic beverage called Ombike: a case study - Uushona, Kleopas Ipinge Twegathetwa (Rhodes University, Faculty of Education, Department of Education, 2013)
One of the purposes of the Namibian curriculum is to ensure cultural inclusivity. That is, it recognises the inclusion of traditional cultural practices and experiences in science lessons where appropriate. Based on my experiences both as a learner and a science teacher, I have noted there is a rapid decline and loss of values in most of our cultural practices and heritages. This triggered my interests to do a study on an Oshiwambo traditional beverage known as Ombike. This study is therefore aimed at enhancing conceptual development, meaning making and understanding of concepts in fermentation and distillation. This study was conducted with my grade 9 learners at a school where I was teaching in Omusati region of Namibia. A community member who served as an expert was also a participant. She was involved more in discussions, interviews and most importantly in showing and demonstrating to the learners how Ombike is made practically. Essentially, the goal of this study was to investigate how the indigenous practice associated with the making of Ombike can be used to support meaning making of fermentation and distillation processes. This research is located within an interpretive paradigm where a qualitative case study was adopted. I consider this methodological framework appropriate in this study because it allowed me to use the following data gathering methods: brainstorming and discussion, observation, semi-structured and focus group interviews, and practical activities worksheet. Multiple methods were used for the purpose of triangulation and validation. An inductive analysis was used to discover data patterns and themes from the data. Moreover, ethical considerations were also taken seriously and all the participants gave informed consent. The findings of the study revealed that brainstorming and discussions were an appropriate strategy in eliciting learners' prior everyday knowledge and experiences on, in particular, the making of Ombike. Furthermore, learner engagement and conceptual development were enhanced. This suggests that contextualisation of knowledge can enhance meaningful learning if it is properly planned. It was also found that practical activities in conjunction with mind maps helped learners to make meanings of scientific concepts. Based on my research findings, I therefore recommend the following three aspects: the consideration of learners` prior knowledge and experiences; contextualising knowledge through use of indigenous knowledge; and the learners' active involvement in practical activities with an emphasis on key scientific concepts to be developed. That is, there is a need to teach for conceptual understanding.
Keywords: Science -- Study and teaching (Secondary) -- Namibia -- Omusati -- Case studies; High school students -- Namibia -- Omusati -- Social life and customs -- Case studies; Education, Secondary -- Namibia -- Omusati; Brewing -- Study and teaching -- Namibia; Ovambo (African people) -- Namibia -- Social life and customs